The influence of intervening variables and subjective norms on the adoption behavior of small scale farmers in South Africa and Lesotho - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.